AQA A-Level Chemistry - McFarland, Alyn G.; Quigg, Teresa; Henry, Nora (London : Hodder Education, 2019)
Develop and learn to apply your knowledge, progressing from basic concepts to more complicated Chemistry, with worked examples, practical activities and mathematical support in this updated, all-in-one textbook for Years 1 and 2. Written for the AQA A-level Chemistry specification, this revised textbook will: - Provide support for all 12 required practicals with activities that introduce practical work and other experimental investigations in Chemistry. - Offer detailed examples to help you get to grips with difficult concepts such as physical chemistry calculations. - Helps to improve mathema.
Includes index.
"EBSCO evaluates our products based on the Web Content Accessibility Guidelines (WCAG) and the related Section 508 and EN 301 549 regulations in the US and EU. Most EBSCO products are substantially conformant with WCAG 2.2 level AA." Source: https://connect.ebsco.com/s/article/EBSCO-VPATs?language=en_US. Last accessed April 22, 2025.
Description based on online resource; title from digital title page (viewed on December 23, 2019).
Master record variable field(s) change: 050, 082
Keywords: Chemistry -- Examinations, questions, etc; Electronic books